Role of ferric carboxymaltose in battle with anemia among north Indian pregnant women - Verma, Urvashi; Bharati, Sadhana; Jain, Meena; Asha; Singh, Saroj; Garg, Ruchika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anemia among pregnant women is a serious global health concern. Anemia is a major hematological, nutritional deficiency but still a manageable health problem among the pregnant women and very common in developing countries like India in under privileged population. Increased morbidity and mortality is seen in pregnant women and their foetuses suffering from anemia. Aim of this study was to study safety and efficacy of injection ferric carboxymaltose in pregnant women with iron deficiency anemia. Methods: This is a Prospective interventional comparative randomized study carried among antenatal women in the Department of Obstetrics and Gynaecology, S. N. Medical College, Agra from (May 2021-October 2022), comprised of 200 pregnant women divided into two groups. Group A-100 antenatal women were transfused with iron sucrose (IS), Group B-100 antenatal women were transfused with ferric carboxymaltose (FCM). Results: In FCM group after 3 weeks of post transfusion hemoglobin level was 10.5±0.44 and in iron sucrose group it was 9.9±0.59 (p=0.0001). 6 week post transfusion hemoglobin level in FCM group was 11.37±0.62 and in iron sucrose group it was 10.45±0.59 (p=0.0001). Average rise in hemoglobin in FCM group after 3 week post transfusion was 2.9±0.02 and after 6 week it was 3.77±0.16. In iron sucrose group at 3 week it was 2.1±0.06 and at 6 week it was 2.65±0.04. The average rise in hemoglobin level was greater among patients of FCM compared to Iron sucrose group. Conclusions: Ferric carboxymaltose was safe and more effective in treatment of iron deficiency anaemia in pregnant women as compared to iron sucrose with lesser side effect and better patient compliance.